Health-related quality of life in patients treated with en bloc resection for primary tumors of the spine - Noli, Luigi Emanuele; Alcherigi, Chiara; Griffoni, Cristiana; Pesce, Eleonora; Rosa, Simona; Evangelisti, Gisberto; Pipola, Valerio; Davassi, Paolo Francesco; Monetta, Annalisa; Barbanti Brodano, Giovanni; Terzi, Silvia; Ghermandi, Riccardo; et al. (Frontiers in Oncology, 2024)
Study designRetrospective analysisObjectiveThe aim of this study is to evaluate the functional outcomes and the health-related quality of life (HRQOL) in patients undergoing en bloc resection of spinal tumor.Summary of background dataEn bloc resection in the spine is a surgical procedure designed to completely remove a tumor in one piece, with wide margins preserved, in order to reduce the risk of local recurrences. This demanding procedure has been shown to improve local control and survival rate, besides a relatively high morbidity.MethodsBetween 2016 and 2021, 70 patients underwent en bloc resection surgery for a primary spine tumor and 38 came out to be eligible for this analysis. Eligibility criteria include at least one follow-up visit within a two-year period from surgery and Patient Reported Outcomes evaluation collected prospectively at baseline and at least one follow- up in the range 4-24 months. The outcome variables (EQ5D Numeric Scale and Index, SF36 scores and NRS score) were analyzed with multilevel linear mixed-effects regression. Baseline- (age, gender, localization, histotype, number of levels of resection, previous surgery) and time-dependent covariates (adverse events, spinal cord damage) were included.ResultsBeside a slight improvement of all the scores, no significant differences were found between baseline and follow up times for EQ-5D-3L Numeric Scale and Index and for SF-36 Standardized Physical component. SF-36 Standardized Mental component appeared to be significantly better at 12-month FU compared to baseline. Ultimately, age over 50 years old and the occurrence of adverse events emerged to be as the two main factor determining worsening in several HRQOL scores. Pain came out to be significantly reduce at 24-month compared to baseline.ConclusionsThe aim of en bloc resection in the treatment of primary spinal tumors is to improve survival rates and reduce local recurrences. Despite its radicality, our preliminary results suggest that patients experience a slight to moderate improvement postoperatively compared to their preoperative perceived health status.